Clear Cell Sarcoma: A Military Case Series - James D Baker; Mason Adams; Josiah Snowden; Megan Barney; James Albright; Gavin Mills; Dustin O Lybeck (Military Medicine, 2026)
Abstract Background Clear cell sarcoma (CCS) is a rare soft tissue sarcoma that primarily affects individuals ages 20-40. It typically presents as a slow-growing, often painless, mass in the extremities. Wide resection is the mainstay of treatment, though local recurrence and metastatic disease are common despite surgery. This case series highlights our experience treating CCS within the military population. Materials and Methods This is a retrospective case series of 3 patients treated at our institution between 2016 and 2026 with biopsy-confirmed CCS. Median survival, local recurrence, and incidence of metastatic disease are reported. Results Three male patients aged 17, 21, and 24 years were diagnosed with genetically confirmed CCS of the thigh. One patient was local to our institution’s area, and the remaining 2 were stationed across the country and therefore underwent initial workup at other hospitals. Tumor size ranged from 5.7 to 14.6 cm, and all lesions demonstrated an EWSR1-ATF1 translocation. Two patients presented with regional nodal metastases at diagnosis, while 1 developed nodal metastasis 6 months after treatment. All patients underwent multimodal therapy consisting of radiation therapy and surgical resection, with 2 receiving prophylactic carbon fiber intramedullary nail fixation. Postoperative complications included wound dehiscence in 2 patients and vascular graft occlusion in 1 patient. Despite additional systemic therapy, all patients developed progressive metastatic disease, including lymph node, pulmonary, and spinal metastases. Overall survival following diagnosis was 12, 12, and 21 months, respectively, with all patients ultimately succumbing to disease. Conclusions CCS is an aggressive tumor with a high rate of local recurrence and metastatic disease. Overall survival is poor, and prompt treatment and early referral to an orthopedic oncologist are paramount to improve patient outcomes. Military providers should be aware of this rare entity, as it primarily affects military-age men and women.